2009
DOI: 10.1509/jimk.17.4.24
|View full text |Cite
|
Sign up to set email alerts
|

When Does International Marketing Standardization Matter to Firm Performance?

Abstract: The topic of standardization of international marketing programs represents an important issue faced by managers of global firms and has attracted significant research attention. Although previous research has established that standardization enhances performance outcomes, more recent theorizing suggests that this may not always be the case. However, empirical investigators have paid little systematic attention to moderating conditions. The major purpose of this article is to investigate the organizational fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 99 publications
2
127
1
1
Order By: Relevance
“…Yet accumulated results do not show support for adaptation over standardization, or vice versa. Drawing on insights from strategic management (Zajac, Kraatz, and Bresser 2000), scholars have shown that the appropriateness of a particular marketing program can be defined in terms of its "fit" with environmental factors (Schilke, Reimann, and Thomas 2009). The contingency theory of fit tests whether more than one strategy maximizes performance across a sample of firms, on the basis of their various environmental conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet accumulated results do not show support for adaptation over standardization, or vice versa. Drawing on insights from strategic management (Zajac, Kraatz, and Bresser 2000), scholars have shown that the appropriateness of a particular marketing program can be defined in terms of its "fit" with environmental factors (Schilke, Reimann, and Thomas 2009). The contingency theory of fit tests whether more than one strategy maximizes performance across a sample of firms, on the basis of their various environmental conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both approaches entail identifying the precise functional form between contingency and response variables (e.g., extent of marketing strategy adaptation for each environmental variable) needed to augment performance variables. Fit as moderation has proved useful in identifying specific, theoretically robust contingency relationships (Schilke, Reimann, and Thomas 2009), even if the results of moderation testing applied to the adaptation issue have been inconsistent (Xu, Cavusgil, and White 2006). Fit as matching is a response to the reductionism (i.e., overly pragmatic specificity) of moderation, insofar as it assumes that firms are surrounded by an array of contingencies that require simultaneous examination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pursuing a policy of using uniform marketing mix variables across national markets becomes available to firms through marketing standardization (Schilke et al, 2009;Zou & Cavusgil, 2002). In other words, the homogeneous needs and preferences of consumers enable firms to implement similar marketing strategies across multiple countries.…”
Section: Marketing Standardization and Performance On International Mmentioning
confidence: 99%
“…Firms should choose strategies that best enable them to apply their limited resources to increase sales and maintain their competitive advantage in a global context (Schilke, Reimann, & Thomas, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation